Nilai Perusahaan pada Struktur Modal Optimal PT. Trans Marga Jateng dan PT. Jasamarga Surabaya Mojokerto Tahun 2020 - Aruji Murtianto; Muhammad Taufik Akbar; Nora Sri Hendriyeni (Research Center and Case Clearing House PPM School of Management, 2021)
In order to maintain the company's ability to fulfill its liabilities, PT. Jasa Marga (Persero) Tbk will takes a corporate action strategy to strengthen capital structure for the Toll Road Subsidiaries (/APJT). APJT selected are PT. Trans Marga Central Java (/PT. TMJ, is the operator of Semarang-Solo toll road) and PT. Jasamarga Surabaya Mojokerto (/PT. JSM, is the operator of Surabaya-Mojokerto toll road) because of its capability to fulfill their solvents. Corporate action strategy done by analyze related with company performance baluation, optimal capital structure analysis. For Company performance valuation, analyze is done with company's financial ratios. From the calculation and analysis of profitability ratios; liquidity ratios and solvency ratios, PT. TMJ and PT. JSM during year 2015-2019 showed fair good performance. The composition of the capital structure to obtain optimal value for PT. TMJ and PT. JSM are range from 60:40 to 30:70 for the composition of debt and equity. The results of the company valuation using Discounted Cash Flow (DCF) method show that the company value of PT. TMJ, with a capital structure composition of 60:40 worth IDR. 25,862,- /share and with a capital composition of 70:30 share value of PT. TMJ in the amount of IDR.10,418,- /share. As for PT. JSM with a capital structure composition of 60:40 is IDR. 2,709,- /share and with a capital composition of 70:30 the share value of PT. JSM is IDR. 911,- /share. From analyze result, Management should pay more attention in capital expense due its effect in Optimizing Capital Structure, then from that Optimal Capital structure, APJT can reduce debt portion dan increasing uts equity portion through several strategy